2011
DOI: 10.1007/s11255-011-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Good response to HBsAg vaccine in dialysis patients is associated with high CD4+/CD8+ ratio

Abstract: High skin test anergy rate and low seroconversion rate after hepatitis B vaccination are important problems in patients on dialysis. Females, younger patients, and patients with higher CD4+/CD8+ ratio have better HBsAb antibody response to hepatitis B vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…What’s more, a positive correlation was observed between the SI and IgG level, indicating that both quantity and function of T cells are associated with immunological effect of HBV vaccine. Previous studies have shown that good antibody response to HBV vaccine is associated with higher CD4 + T cell counts [29], [30] or high CD4 + /CD8 + ratio [31]. Moreover, zinc is required for the regeneration of CD4 + T cells [32], [33], and zinc deficiency is associated with significantly decreased CD4 + /CD8 + ratio and lowered B cell numbers [34], which is similar to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…What’s more, a positive correlation was observed between the SI and IgG level, indicating that both quantity and function of T cells are associated with immunological effect of HBV vaccine. Previous studies have shown that good antibody response to HBV vaccine is associated with higher CD4 + T cell counts [29], [30] or high CD4 + /CD8 + ratio [31]. Moreover, zinc is required for the regeneration of CD4 + T cells [32], [33], and zinc deficiency is associated with significantly decreased CD4 + /CD8 + ratio and lowered B cell numbers [34], which is similar to our findings.…”
Section: Discussionsupporting
confidence: 90%
“…However, there was significant heterogeneity of the studies included in the meta‐analysis; this limitation was acknowledged by the authors. A few small trials in the Asian population found a similar association with age, whereas conflicting results were noted in some others . Additionally, Lin and colleagues reported that nonresponse to the vaccine was associated with infection‐cause mortality in ESRD patients, although there was no impact of the immune response on the 5‐year survival rate.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…A growing body of literature has recognized a number of other factors relating to the efficacy of the hepatitis vaccine in patients with kidney disease. Immune deficiency in the uremic milieu, malnutrition , male gender , hepatitis C virus infection , and diabetes mellitus have been associated with a diminished vaccine response albeit some studies refute these associations . Some previous studies have demonstrated that seroconversion rates correlate with the stage of CKD , substantiating the recommendation for vaccinating patients with CKD before they become dialysis dependent .…”
Section: Hepatitis Bmentioning
confidence: 99%
“…In HD patients, the activity of NK cells is either lowered or unchanged [17]. A higher CD4/CD8 ratio, a marker of Ig production by B cells, is also associated with a better serological response to hepatitis B vaccination [18].…”
Section: Effects On Immune Responsementioning
confidence: 99%